Pengaruh Label Halal dan Promosi Terhadap Keputusan Pembelian Produk Kosmetik Scarlett - Rohmah, Aniyatur; Habibi, Azwar (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
The research aimed to determine the influence of halal labelling and promotion on purchasing decisions for Scarlett cosmetic products among these students. The study employed a multiple linear regression analysis using SPSS version 21, with primary data collected through questionnaires from a sample size of 159 Sharia economics students. The results showed that both halal labelling and promotion had a positive effect on purchasing decisions. The F test indicated that the simultaneous influence of halal labelling and promotion on purchasing decisions was significant. Moreover, the t tests revealed that both the halal labelling variable and the promotion variable had a positive and significant effect on purchasing decisions. The coefficient of determination (R2) showed that 46.8% of the regression model could explain the purchasing decisions, with the remaining 53.2% being influenced by other variables not examined in this study.